Review of the genus Ceratovacuna (Hemiptera: Aphididae) with descriptions of five new species from China - Jiang, Liyun; Chen, Jing; Guo, Kun; Qiao, Gexia (Zootaxa, 2015)
The genus Ceratovacuna Zehntner, 1897 (Hemiptera: Aphididae: Hormaphidinae) is reviewed for the first time in China, with the descriptions of five new species, C. angusticorna Qiao sp. n., C. beijingensis Qiao sp. n., C. imperata Qiao sp. n., C. multiglandula Qiao sp. n., C. separata Qiao sp. n. and four new records for China, C. graminum (van der Goot, 1917), C. keduensis Noordam, 1991, C. panici (van der Goot, 1917) and C. uscare (Tao, 1964). The molecular analyses based on COI and Cytb sequences both supported the status of these new species.